Molecular Cloning of large DNA Fragments of The Sal t Tolerant wild Tetra ploid bermudagrass Cynodon Dactylon L. Using A Bacteriophage Cloning Vector 2. Ligation a nd in vitro packaging of The Recombinant Phage DNA Molecules - lbâ€¢â€¢aheem, S. A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This  paper represent  the second  step  i n  a molecular clon i ng program ai ming to clone large DNA  fiÂ·agmen ts of the sal t tolerant  bermudagrass (Cyrwdon  dactylon  L.)  DNA  usi ng  the  bacteriophage  (EM13L3) as    a vector.In th is  work, a yield of about  I 00  g bacteriophage  DNA  per one  liter culture.was obtained  with.a  purity ranging between (1.7-1.8). The vector JJNA  v.as  completely   double   digested   with  the  restriction   enzymes llamHI   and  EcoRI,  followed  by  purification  of  vector  arms. llacteriophage  anns   were  also   efficiently   ligated   with   the   partially digested   bermudagrass  DNA  (prepared  earlier).  The  optimum   ligationratio  or arms:  inserts  (EMBL3:  bermudagrass)   was  found  to  be  4: Irespectively. The  recombinant  DNA  was successfu lly in vitro packaged and     plated  on  a P2  lysogen  E. coli (strain  N M539).  An efficiency  of about  1.3x I 06 pfu/ tg recombi l1311l     ph age DNA was determined  in these ex periments.